Microvascular Adaptations to Muscle Stretch: Findings From Animals and the Elderly - Hotta, Kazuki; Muller-Delp, Judy (Frontiers in Physiology, 2022)
Microcirculation in skeletal muscle is disturbed with advancing aging, causing limited capillary blood flow and exercise incapacity. Muscle stretch has been widely performed in physical therapy, sports medicine, and health promotion. However, the effect of stretch on microvascular reactivity and muscle blood flow remains unknown. This review focuses on stretch-induced microvascular adaptations based on evidence from cultured cells, small animals, and human studies. Vascular endothelium senses and responds to mechanical stimuli including stretch. This endothelial mechanotransduction potentially plays a vital role in the stretch-induced microvascular adaptation alongside hypoxia. Aging impairs microvascular endothelial function, but muscle stretch has the potential to restore it. Muscle stretch may be an alternative to improve vascular function and enhance exercising blood flow, especially for those who have difficulties in participating in exercise due to medical, functional, or psychological reasons.